Subject Content of Competency-Based Curriculum and English Language Teachers’ Attitudes Towards Teaching Reading Skills in Secondary Schools in Mpigi District, Uganda - Wasagali Rachel; Isa Muhammad Sulaiman; Kintu John (Journal of Research in Education and Pedagogy, 2026)
Teacher attitudes toward subject content in Competency-Based Curriculum (CBC) are generally recognized as a decisive factor in the success of any educational reform. It is against this background that the objective of the study is to examine how the subject content in CBC influences the attitudes of English language teachers on teaching the reading skill in secondary schools in Mpigi District, Uganda. The study used a mixed-methods research design that combined both quantitative and qualitative methods, in which 148 respondents (English language teachers and Heads of English Department) were involved in completing structured questionnaires and interviews. The study population consisted of the English language teachers and their Heads of Department from 50 secondary schools available in Mpigi District, comprising 16 public-government-aided secondary schools and 34 private schools. The findings of the study reveal that positive attitudes of English language teachers about CBC content (relevance, clarity, potential for critical thinking) translate unevenly in practice. Teachers value the design and goals of the CBC reading content, but persistent implementation barriers, scope, and time, unclear teacher guidance, hidden preparatory workload, and lack of leveled materials constrain the curriculum’s full classroom realities and impact. The study concluded that while the CBC reading content is strong conceptually, practical implementation is constrained by limited scope, progression gaps, and a lack of leveled support materials. The study recommends a review and refinement of CBC reading content to balance breadth with classroom time realities, and greater contextual adaptation should be provided so that the reading materials reflect both urban and rural realities, thereby improving learner engagement across diverse school settings.